Subacromial osteochondroma: A rare cause of impingement syndrome. (2015) - Çıtlak, Atilla; Akgün, Ulaş; Bulut, Tugrul; Aslan, Cihan; Mete, Berna Dirim; Şener, Muhittin
Highlights: Subacromial impingement syndrome is one of the most common disorders of shoulder. Osteochondromas arising under the acromion rarely cause impingement syndrome. The diagnosis of subacromial osteochondroma should be considered in any patient with shoulder impingement syndrome and good functional results can be expected following total excision. Abstract: Introduction: Subacromial impingement syndrome is one of the most common disorders of shoulder. Scapula is a very rare site for osteochondromas, and osteochondromas arising under the acromion cause impingement syndrome. Presentation of case: We presented 34-year old female patient with subacromial impingement syndrome secondary to osteochondroma. She had received conservative treatment several times in other clinics. The osteochondroma causing impingement was not diagnosed. Physical examination of the right shoulder revealed 90° flexion, 70° abduction, 20° external rotation and internal rotation to sacrum. X-ray, CT and MRI of the shoulder was obtained. Osteochondroma of the acromion (35 × 33 × 25 mm) causing impingement was detected. The osteochondroma of acromion compressed, displaced and ruptured the supraspinatus tendon. Also an osseous prominence of glenoid was detected during shoulder arthroscopy, and it was removed arthroscopically. The giant osteochondroma of acromion could not remove arthroscopically due to the size of the lesion, and it was removed totally through a mini open approach. Histopathological examination confirmed the diagnosis of osteochondroma. Discussion: Scapular, clavicular and humeral osteochondromas cause impingement syndrome. Osteochondroma should be treated with total excision. Recurrences can be seen due to insufficient removal of osteochondromas. We think that, total excision is important to prevent recurrence. Subacromial osteochondroma is a very rare cause of impingement syndrome, and if it isn't diagnosed early it limits shoulder movements, causes severe shoulder impingement and rotator cuff tear. Conclusion: The diagnosis of subacromial osteochondroma should be considered in any patient with shoulder impingement syndrome and good functional results can be expected following total excision.